THE CRIMINAL LIABILITY OF CORPORATE TAXPAYER IN THE PERSPECTIVE OF TAX LAW REFORM IN INDONESIA - Henry Dianto Pardamean Sinaga (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractThe raise of tax evasion by corporation has been detrimental of state revenue, so it is required to ascertain the persona in crime and formulation of in absentia investigation of the corporate taxpayer crime in Indonesia. This legal descriptive-comparative-analytical research generates that corporate an/or human can be accounted for either jointly or individually in tax crime undertaken of the corporate taxpayer. Furthermore, in absentia investigation of the corporate taxpayer crime could be filed as long as fulfilling formil and material requisite. It is expected the affirmation of  any person definition and corporate taxpayer crime categories in the future tax reform framework. IntisariMaraknya penggelapan pajak oleh badan hukum sangat merugikan pendapatan negara sehingga perlu untuk mengetahui pertanggungjawaban pidana dan formulasi penyidikan in absentia pidana yang dilakukan Wajib Pajak Badan di Indonesia.  Penelitian yang bersifat deskriptif – komparatif - analitis ini menghasilkan bahwa badan hukum dan/atau manusia dapat dipertanggungjawabkan baik bersama-sama atau sendiri-sendiri dalam pidana yang dilakukan Wajib Pajak Badan.  Selain itu,  penyidikan in absentia dalam pidana Wajib Pajak Badan di Indonesia dapat diberkaskan dengan tetap memenuhi syarat formil dan materiil.  Dalam kerangka pembaharuan hukum pajak diharapkan terdapat penegasan dalam undang-undang perpajakan terhadap unsur setiap orang dan kategori pidana Wajib Pajak Badan.